EFFECT OF - SIVBALATHAVAN, YHAGUNAN (2018)
Enhanced Oil Recovery (EOR) is a tertiary method that is done after the primary and secondary method. Although there are many applications available in EOR, researchers are constantly researching in the usage of nanotechnology for the EOR application because of the particles’ special properties, cost reduction as well as being environmental friendly. There are many advantages and disadvantages of the usage of nanotechnology in EOR. The reason behind this is because of different materials of nanoparticles gives different types of effect towards the application of EOR. This research paper consists of Alumina (Al2O3) nanoparticles that was dispersed into brine together with Zinc Oxide (ZnO) to formulate